Testing of mapping approaches for estimation of 100-year maximum daily precipitation totals in the upper Hron River basin - SZOLGAY, Ján; PARAJKA, Juraj; KOHNOVÁ, Silvia; HLAVČOVÁ, Kamila; LAPIN, Milan; FAŠKO, Pavol (Contributions to Geophysics and Geodesy, 2021)
The 100-year maximum daily precipitation totals for rainfall-runoff studies and estimating of flood hazard were mapped. The main objective of this study was to discuss the quality and properties of maps of design precipitation with a 100-years return period. Four approaches to the preprocessing of annual maximum 24-hour precipitation data were used. The first method was the direct mapping of at-site estimates of distribution function quantiles. In the second method, the daily measurements of the precipitation totals were interpolated into a regular grid network, and then the time series of the annual maximum daily precipitation totals in each grid point of the selected region were statistically analysed. In the third method, the spatial distribution of the design precipitation was modeled by quantiles predicted by regional precipitation frequency analysis using the Hosking and Wallis procedure. Homogeneity of the region of interest was tested, and the index value (the mean annual maximum daily precipitation) was mapped using spatial interpolation. Quantiles were derived through the dimensionless regional frequency distribution estimated by using L-moments. The kriging interpolation method was applied in all of these three approaches. The mapping approaches were tested on the daily precipitation measurements at 23 climate stations from 1961–2000 in the upper Hron basin in central Slovakia. In the fourth method, the estimation of 100-year maximum daily precipitation at 557 stations in Slovakia was the basis for the construction of expert's hand drawn isohyets of design maximum daily precipitation totals. The part of the map for the upper Hron basin was selected and compared with previous mapping approaches.